2008
DOI: 10.1016/j.ejheart.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐analytic evaluation of the clinical effectiveness and cost‐effectiveness of management programmes in chronic heart failure

Abstract: Background and aims: While management programmes (MPs) for chronic heart failure (CHF) are clinically effective, their cost-effectiveness remains uncertain. Thus, this study sought to determine the cost-effectiveness of MPs. Methods and results:We developed a Markov model to estimate life expectancy, quality-adjusted life expectancy, lifetime costs, and the incremental cost-effectiveness of MPs as compared to standard care. Standard care was defined by the EuroHeart Failure Survey for Germany, MP efficacy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 24 publications
2
47
0
1
Order By: Relevance
“…They find that the patients under disease management have a longer lifespan and, hence, produce higher future costs to the system. Göhler et al 36 and Miller et al 37 conduct similar studies and report comparable results. The US Congressional Budget Office 38 has expressed concern that, while interventions are appropriate, from a budgeting perspective the chronic disease management interventions may contribute to projected increases in demand for medical services, and hence costs to the overall system, in the long run.…”
Section: Background and Literature Reviewsupporting
confidence: 59%
“…They find that the patients under disease management have a longer lifespan and, hence, produce higher future costs to the system. Göhler et al 36 and Miller et al 37 conduct similar studies and report comparable results. The US Congressional Budget Office 38 has expressed concern that, while interventions are appropriate, from a budgeting perspective the chronic disease management interventions may contribute to projected increases in demand for medical services, and hence costs to the overall system, in the long run.…”
Section: Background and Literature Reviewsupporting
confidence: 59%
“…Nineteen studies reported QALYs. [21,22,27,32,33,[35][36][37]39,40,42,[44][45][46][48][49][50][51][52] Most studies presented a reasonable number of deterministic sensitivity analyses on key model parameters. Many recent studies also performed probabilistic sensitivity analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Many recent studies also performed probabilistic sensitivity analyses. [26,27,33,35,[38][39][40]42,44,46,47,49,51,52] Subgroup analyses for different target populations [35,37,42] and device applications [39] were performed on a limited basis. Eight studies reported validation of the results, including cross-model comparison, face validity through presentation of results to experts or comparison of model results against independent data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HC was consequently the most apparent cost driving factor which after all was remarkable since the intervention was executed in a PHC-based setting without directly focusing on HC. There are data showing that HFMPs in PHC is cost-effective compared to conventional standard care of HF (132).…”
Section: The Resource Utilizationmentioning
confidence: 99%